Behring Sea: memoranda, proposed regulations [electronic resource]. - Great Britain. Foreign Office. ([S.l. : s.n., 1893)
Manuscript notes and corrections. Caption title. Attributed to Great Britain. Foreign Office --A bibliography of British Columbia / B. J. Lowther. Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44